Labour Laws in Preindustrial Europe The Coercion and Regulation of Wage Labour, c.1350-1850 - Whittle, Jane; Lambrecht, Thijs (People, Markets, Goods: Economies and Societies in History, 2023)
Explores the variety of legal and regulatory regimes that existed in Western Europe to control labour and how workers experienced those controls. Many economic historians have assumed that labour in Western Europe was 'free' after the end of serfdom in the fifteenth century. These assumptions are increasingly being questioned and labour laws have been identified as creating significant restrictions on workers' freedom. This collection is the first book to look at labour laws across Western Europe from a longer-term perspective. It is interdisciplinary in nature bringing together studies in social, political, economic and legal history. Elements of labour legislation appeared before the Black Death, but were strengthened afterwards particularly in places and periods where labour became scarce. The collection focuses on the rural economy in the late medieval and early modern period. It provides a series of studies which introduce a range of approaches to labour regulation and the very idea of labour across Europe. Uniquely, the collection offers observations on the impact of labour laws on everyday social relations. Attempts to regulate work and labour varied widely: in places they amounted to wishful thinking on the part of the regional authorities, whereas elsewhere they could impose severe limitations on individual freedoms. Contributors: Davide Cristoferi, Theresa Johnsson, Thijs Lambrecht, Charmian Mansell, Francine Michaud, Hanne Østhus, Raffaella Sarti, Carolina Uppenberg and Jane Whittle.